Memory- and energy-efficient VLSI architectures for 2-D discrete wavelet transformation - Hu, Yusong (2015)
DWT has been applied to various applications such as image analysis, video processing and computer graphics. The conventional general purpose processors are unable to satisfy the hunger for computational speed and the demand for energy efficiency at the same time. Therefore, specifically designed VLSI DWT architectures are required to tackle the issue. In this thesis, the architecture for 2-D DWT is studied and novel 2-D DWT architectures are proposed which achieve high memory and energy efficiency. Broadly, the research is motivated by improving two most important performance metrics, namely silicon area and energy efficiency. The thesis details the development of the proposed data scanning methods, the computation scheduling, the evaluation of energy efficiency, the proposed hardware architectures, the performance evaluation of the architectures and the comparison with the state-of-the-art designs.